Antibacterial Activity of Terrestrial Snail Mucus: A Review - I Gusti Ayu Agung Septiari; Ni Putu Aryati Suryaningsih (Yayasan Baru Haji Samsudin, 2024)
Antibiotic resistance is one of the major health problems faced by various countries in the world. Due to the urgency of the antibiotic resistance problem, efforts to identify new lead compounds from new sources and analysis to determine their bioactivity are urgently needed for antibiotic development. One of the invertebrate organisms studied in relation to its potential to produce secondary metabolites that have antibacterial properties is the Gastropoda class which is included in the Mollusca phylum. Gastropoda consists of more than 80 thousand species and differs from other classes in the Mollusca phylum because of its torso body. Gastropoda has 3 sub-classes, namely: Prosobranchia, Opistobranchia, and Pulmonata. One of the land Gastropod species is snails, both those with shells (snails) and naked snails (slugs) which are included in the Pulmonata sub-class. Snail mucus is used as a traditional medicine and also as an innovative natural product to treat various health problems. Since Gastropods include a large number of species that live in various ecosystems, but research on the antibacterial potential of their secondary metabolites is still limited, this review aims to summarize research that explores the antibacterial effects of secondary metabolites in mucus produced by species in the class of Gastropods that live on land (terrestrial gastropoda) especially various species of terrestrial snails. The preparation of this review article uses a literature study method with a systematic approach. The articles used are international articles that discuss the antibacterial activity of secondary metabolites in mucus produced by snails. Articles were obtained from the PubMed database using the keywords snails AND antibacterial from the period 2000 to 2023, the period before 2000 was excluded due to the very minimal number of articles. The results obtained from the journal review that has been carried out are the presence of bioactive components such as peptides, glycopeptides, and other secondary metabolites found in the mucus of several species of land snails. These bioactive components have antibacterial activity against gram-positive and gram-negative bacteria.